Application of Neuro- Marketing for Developing Products and Services - Arshi Naim (Web of Journals Publishing, 2023)
This is an extended research focus on the application of neuro marketing for developing products and services. Psychiatry is increasingly embracing functional magnetic resonance imaging (fMRI) and other neuro-technologies, which carry the promise of revealing the underpinnings of emotions and social interactions. Neuro- Marketing (NUMKTG) has brought a revolution in the field of marketing. The adoption of NUMKTG has resulted in better understanding of consumer behaviour. The thrust for increasing business and branding through brains has a great impact to marketing. NUMKTG, being an interdisciplinary research area has emerged as a solution for achieving better understanding of consumer behaviour. For sustainable future and increased business, NUMKTG techniques need sincere attention. Although it is an active research area and there are many solutions for achieving efficiency, existing approaches ignore the integrated framework for understanding neurometric data. The real challenge is to maintain a satisfactory performance level without raising investments. This study provides a wide-ranging study of literature. This study explains the integration of technologies and marketing concepts and their applications for enhancing effective consumer behavior.
Keywords: Consumer behavior, Neuro- Marketing, Emotion, Neuroimaging, Non-Neuroimaging techniques